Qualitative study: Caregiver's perception of the social-emotional development of children given infant massage as a daily affective touch - Widiani, Ni Nyoman Ayuk; Chania, Made Pradnyawati; Sugiartini, Ni Ketut Ayu; Widiastuti, Ni Made Rai; Febriyanti, Ni Made Ari; Adnyani, Ni Wayan Sukma (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background: Affective touch aims to convey affection to children. This touch is closely related to emotional needs and social bonds, which strengthen relationships between individuals. Children in orphanages often experience a lack of affective touch, which causes persistent stress.Objectives: To determine caregivers' perceptions of the social-emotional development of babies and children who receive baby massage as daily affective touch at the Metta Mama and Maggha Foundations.Methods: This research is a qualitative study with a phenomenological approach. The sample consisted of 25 caregivers, using the total population. Data was collected through focus group discussions (FGDs), with each group consisting of 8-9 caregivers.Results: Some participants have the perception that a socially healthy child is a child who is able to adapt and interact with others, some participants have the perception that children need social-emotional aspects such as the need for affection, attention, the need to be loved, a sense of security, and a desire to be understood, some participants have the perception that the role of caregivers is very large because it replaces the role of parents, most participants said that baby massage has been done on children aged 0-6 months, some participants have the perception that baby massage can affect the calmness, comfort of babies so that they can be more optimal in carrying out daily activities, some participants have the perception that children who are socially-emotionally healthy behave more understandingly, confidently and more quickly accept the information given and all participants have the perception that it is very important to apply parenting patterns with touch, because of the lack of touch in orphanages.Conclusions: According to caregivers at the Metta Mama & Maggha Foundation, it is important to implement parenting patterns with touch in the form of baby massage as Daily Affective Touch in children's social-emotional development